Uma nova etapa: juventude e experiências de ingresso no ensino médio - Souza, Luiz Gustavo Silva (2007)
Nowadays, high school education is expanding in Brazil in terms of number of students. Current ways of social and labor organization demand high levels of qualification and impose new problems to the construction of democracy in human relations. To understand and correct these problems, education must be analyzed not only from a quantitative perspective, but also from a qualitative one. It is important to study the relations between adolescents and schools and to investigate students representations and activities. The present work aims at understanding the first high school education experiences in low SES students, considering possible transformations in their social representations and identities. A hundred and twenty students participated in this research: 61 girls and 59 boys, aged 14 to 16 years old, freshmen of a public high school located in Viana, Brazil. We collected data in two different moments: February 2006 (beginning of the school year) and September 2006. The method included questionnaires, free evocation techniques and semi-structured interviews. For data analyses, we used content analysis and the EVOC software. We compared the results obtained in the two moments of data acquisition, based on period (beginning and half of the school year) and gender. In the beginning of the year, students associated the school entirely with positive values, such as maturity and promising future . Students hoped to study more and to become more responsible and concerned about the future. However, they did not expect to find a favorable environment for youth participation. In September, positive values still existed and were hegemonic, but there were also negative values associated to school. The perception that the school infra-structure was not well used is an example. Other negative perceptions appeared but were less representative: the ideas that the classes were useless, that the teachers were bad and that the professional future was uncertain. School mates were more clearly divided in subgroups. The representation of good teacher included empathy and the ability to contextualize knowledge. Education continued to be perceived mainly as the path to a better future. High school continued to be seen as a new stage of this preparation, which is more demanding and more associated with responsibility. The idea that high school education is important for their professional future was stronger. At the same time, school continued to be faced as naturally tied to heteronomic human relations. Possibilities of active participation in school organization seemed to be weaker. The representation of good student continued to be strongly linked to traditional school values such as obedience and effort. As we compared the two moments (beginning and half of the school year), we verified the existence of two hegemonic paths in high school experiences: submission (to invest in school, to be a good student, to be obedient) and rejection (to despise school rules and processes). We discuss the importance of strategies to produce autonomy in high school education, basing other possibilities for identity construction. The first high school year seems to be a favorable moment to propose those strategies.